The Gamma statechart composition framework: Design, verification and code generation for component-based reactive systems - Molnár, Vince; Graics, Bence; Vörös, András; Majzik, István; Varró, Dániel (2018 IEEE/ACM 40th International Conference on Software Engineering: Companion (ICSE-Companion), 2018)
The Gamma Statechart Composition Framework is an integrated tool to support the design, verification and validation as well as code generation for component-based reactive systems. The behavior of each component is captured by a statechart, while assembling the system from components is driven by a domain-specific composition language. Gamma automatically synthesizes executable Java code extending the output of existing statechart-based code generators with composition related parts, and it supports formal verification by mapping composite statecharts to a back-end model checker. Execution traces obtained as witnesses during verification are back-annotated as test cases to replay an error trace or to validate external code generators. Tool demonstration video: https://youtu.be/ng7lKd1wlDo